Prasasti Turryan menengok bendungan jaman kuno di Turen (Suatu kajian IPS terpadu peninggalan sejarah) - Sinyamin Sinyamin (Universitas Negeri Malang, 2016)
Uncovering the function and role of geography, is useful to (1) cultivate an attitude of awareness and concern for the environment and resources. (2) Increasing Tolerance to socio-cultural awareness for the community. Historical heritage is a vehicle that is suited to make it happen. Turen, ancient city in Indonesia has a history of the area should retain identity, safeguard the environment, natural resources, history, and human. Cultural property need to be cultivated as fixed tepeliharanya environmental sustainability and culture. Potential Geography enables Turen region to develop the area to increase the welfare of society through historical heritage and the possibility of development.Keywords: Geography, History, cultural legacy, Environment, Resources. http://dx.doi.org/10.17977/um022v1i22016p136